Development of an Android-Based Financial Management App to Support Educational Infrastructure Enhancement at Pondok Pesantren Nurul Hidayah in Accordance with SDG 9 - Windarto, Windarto; Martini, Martini; Irawan, Yousep Eka (STMIK Widya Cipta Dharma, 2024)
Technological advancements have significantly transformed human life, with increasing digitalization across various aspects. However, in the context of the Fourth Industrial Revolution, these advancements have disrupted the role of humans, raising concerns about the potential loss of humanity's essence. In response to these challenges, Japan introduced the concept of Smart Society 5.0 in 2019 to mitigate the negative impacts of this disruption by re-establishing humans as the central element in modern life. As a form of community service, the service team developed the program